Determinan Islamic Intellectual Capital Pada Bank Syariah Di Indonesia - Ina Munawaroh; Sigid Eko Pramono; Luqyan Tamanni (DPPM Universitas Pelita Bangsa, 2023)
The purpose of this research is to analyze the effect of Firm Size, Profitability, Leverage and Good Corporate Governance on Islamic Intellectual Capital in Islamic Banks in Indonesia. Analysis of the influence of factors that affect Intellectual Capital using panel data regression method with e-views 9 software and Microsoft Excel program. This study uses data obtained from the company's financial statements & GCG Islamic Banking in Indonesia in the period 2014-2020 And with a samples of 10 islamic banks. The results of the study indicate that the selection of the most appropriate model for the panel data regression method is the fixed effect model with the results of research the variables size, profitability, leverage have a significant effect on Intellectual Capital while the variable Good Corporate Governance (GCG) has no significant effect on Intellectual Capital in Islamic banking companies in Indonesia for the 2014-2020 period.